Understanding China’s fintech sector: development, impacts and risks - Hua, Xiuping; Huang, Yiping (2020)
Financial technology (fintech) is rapidly transforming the economy as well as the financial landscape in China. This paper attempts to shed light on its contributing factors, current state, economic impacts and potential risks. We identify three key drivers for China’s fintech development, namely shortage of supply in formal financial market, strong government support for promoting financial inclusion through digital technology, and more ‘tolerant’ regulatory environment. The greatest value of the Chinese fintech sector is promotion of financial inclusion, enabling a vast number of small- and medium-sized enterprises (SMEs) and low-income households to access to financial services. Existing studies unveil some strong evidences of fintech development improving efficiency, increasing employment and supporting entrepreneurship. In the meantime, there are also serious challenges facing this sector, such as regulatory uncertainties, illegal transactions, data abuse, etc. We conclude the paper by presenting some key takeaways, including several lessons for financial regulation.